Analysis of Company Size and Profitability on Company Value with Corporate Social Responsibility as Moderation - Aprilliyani, Andini; Dwui Maharani , Indah; Pratiwi , Lopa; Purdianto, Ario (Publikasi Indonesia, 2024)
The health of financial performance is a determinant of a company's value. This is reflected as a record of good company performance in carrying out its operations. However, in addition to healthy financial performance factors, corporate social responsibility (CSR) practices are used as a reference for investors in assessing companies to provide funding. This study aims to empirically analyze the effect of profitability and company size on company value with corporate social responsibility as a moderation variable. The population used as the object of observation used is an energy sector company listed on the Indonesia Stock Exchange in 2020 - 2022 using quantitative methods with purposive sampling as a sampling technique. Data analysis techniques using Panel Data Regression Analysis and Moderate Regression Analysis (MRA) with the help of Eviews 12. Based on the findings in the study, that profitability has a positive and significant effect on company value, company size has a negative and insignificant effect on company value, CSR moderation variables moderate the effect of profitability on company value, CSR moderation variables are not able to moderate the effect of company size on company value on company value. Thus, researchers conclude that companies should optimize operations to identify profitable growth opportunities, organizational restructuring or unnecessary bureaucratic cuts to improve operational efficiency, and strengthen their commitment to corporate social responsibility practices as an integral part of their business strategy.